2008
DOI: 10.1038/sj.cdd.4402313
|View full text |Cite
|
Sign up to set email alerts
|

The VHL tumor suppressor and HIF: insights from genetic studies in mice

Abstract: The von Hippel-Lindau tumor suppressor gene product, pVHL, functions as the substrate recognition component of an E3-ubiquitin ligase, which targets the oxygen-sensitive a-subunit of hypoxia-inducible factor (HIF) for rapid proteasomal degradation under normoxic conditions and as such plays a central role in molecular oxygen sensing. Mutations in pVHL can be found in familial and sporadic clear cell carcinomas of the kidney, hemangioblastomas of the retina and central nervous system, and pheochromocytomas, und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(124 citation statements)
references
References 126 publications
(145 reference statements)
3
119
1
1
Order By: Relevance
“…Although these findings complement previous data showing that systemic and nonselective cellular stabilization of HIF protects against ischemic 29,31 and toxic renal injury, 28,30 this study extends these results by demonstrating that Vhl deletion in a specific nephron segment is sufficient to achieve renal protection. Moreover, in contrast to previously published mice with cell type specific inactivation of Vhl, 32 the phenotype of animals with Vhl deletion in TALs was surprisingly normal, indicating that Vhl pathology is context-dependent.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although these findings complement previous data showing that systemic and nonselective cellular stabilization of HIF protects against ischemic 29,31 and toxic renal injury, 28,30 this study extends these results by demonstrating that Vhl deletion in a specific nephron segment is sufficient to achieve renal protection. Moreover, in contrast to previously published mice with cell type specific inactivation of Vhl, 32 the phenotype of animals with Vhl deletion in TALs was surprisingly normal, indicating that Vhl pathology is context-dependent.…”
Section: Discussioncontrasting
confidence: 99%
“…25,26 Previous studies have shown that systemic hypoxia or pharmacologic approaches to stabilize HIF can protect the kidney against subsequent ischemic or toxic injury. [27][28][29][30][31] In addition, Vhl knockout strategies have been successfully applied to stabilize HIF genetically 32 and acute ubiquitous inactivation of Vhl has recently been shown to ameliorate ischemic AKI. 33 All of these approaches have so far not allowed defining the role of specific parts of the nephron in AKI protection.…”
mentioning
confidence: 99%
“…This observation has remained an enigma since this report by Gnarra et al (27) was published in 1997. Vhl −/− mice die during gestation (27), but simultaneous inactivation of both Vhl alleles in kidney epithelial cells similarly failed to induce renal tumorigenesis (28)(29)(30)(31). These experiments are confounded by lack of knowledge about the cell type of origin of ccRCC and restricted Cre expression (28-31); however, as we show, even when Vhl is inactivated in multipotent NPCs, Vhl loss is insufficient for renal tumorigenesis.…”
Section: Discussionmentioning
confidence: 85%
“…To mimic chronic hypoxia, we stabilized hypoxia inducible transcription factors by the deletion of the von Hippel-Lindau protein (pVHL). 10 pVHL mediates oxygen-dependent proteasomal degradation of hypoxiainducible transcription factor-a (HIF-a) protein and thereby, acts as a negative regulator of HIF. 11 Cell-specific deletion of Vhl, therefore, activates HIF-regulated pathways in these cells.…”
mentioning
confidence: 99%